Impact of salpingectomy on the risk and characteristics of ectopic pregnancy after IVF/ICSI in patients with ectopic pregnancy history: A large retrospective cohort study - Xueyi Jiang; Shutian Jiang; Hongyuan Gao; Jing Ye; Yanping Kuang (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Ectopic pregnancy (EP) is a serious clinical gynecological emergency. Patients with EP history are at higher risk of EP resulting from IVF/ICSI (IVF‐EP). Besides, studies have suggested that previous EP treatments may affect the incidence of IVF‐EP. However, this result does not consider possible confounding factors due to the number of previous EP. Therefore, we assessed the impact of salpingectomy on the risk and characteristics of IVF‐EP in patients with different previous spontaneous EP. Material and Methods This retrospective cohort study included 43 647 patients receiving their first IVF/ICSI treatments at our center from January 2013 to June 2022. Cohorts were assigned according to the number of previous spontaneous EP by propensity score matching. After propensity score matching, there were 3252 participants in the no previous EP history cohort (NEP cohort), 3252 in the one EP history cohort (One‐EP cohort), and 1571 in the 2 or more EP history cohort (> = 2 EP cohort). To assess the effect of previous salpingectomy on IVF‐EP, One‐EP cohort and > =2 EP cohort were divided into three subcohorts separately, according to their tubal statuses. Results The IVF‐EP rate was significantly higher in patients with EP history (NEP cohort: 1.3% vs. One‐EP cohort: 2.2% vs. >=2 EP cohort: 2.0%, p = 0.023). In subcohort analysis, patients with different tubal statuses presented no statistical differences in IVF‐EP rate (both in One‐EP cohort and > =2 EP cohort). Considering the interaction between tubal status and number of previous EP, binary logistic regression was performed and it was demonstrated that bilateral salpingectomy might reduce the risk of IVF‐EP in patients with recurrent EP history but increase the risk of non‐tubal IVF‐EP, while the history of spontaneous EP increased both IVF‐EP and non‐tubal IVF‐EP rate. Conclusions Previous EP history was associated with a higher risk of IVF‐EP and non‐tubal IVF‐EP. Salpingectomy reduced the overall risk of IVF‐EP in patients with EP history, while bilateral salpingectomy increased the risk of non‐tubal IVF‐EP.